Radionuclide-Labeled Biomaterials: A Novel Strategy for Tumor-Targeted Therapy - Shu Zhang; Aiyue Zhang; Xunhao Qi; Zongtai Han; Luqi Song; Jiayu Zhou; Guanglin Wang; Ran Zhu; Jianguo Li (Biomimetics, 2025)
This paper presents a comprehensive review of recent advancements in radionuclide-labeled biomaterials for cancer therapy, with a particular focus on the characteristics, production methods, and labeling techniques of α-particle, β-particle, and Auger electron-based radiotherapy. It explores innovative strategies for targeted delivery systems and highlights the advantages of theranostics and combination therapies. The application of radionuclide-labeled biomaterials in various cancer types, including prostate cancer, breast cancer, neuroendocrine tumors, gliomas, and melanoma, is systematically summarized. Furthermore, the article critically examines current technological bottlenecks and challenges in clinical translation, while proposing future directions such as AI-assisted dose optimization and multimodal combination therapies. This review provides essential theoretical foundations and practical insights to facilitate the clinical translation of radionuclide-labeled biomaterials.